Developing Nursing Geography with an Ecological Lens - Alysha Jones; Jacqueline Avantay Strus (York University Libraries, 2022)
In this paper, we propose that community health nursing is a promising context for ecologically inclusive and "place-sensitive" (Andrews, 2002) nursing practice. With a strong grounding in social justice, we believe that Canadian community health nurses have the power to create a differential space of research and practice for environmental justice and planetary health thereby challenging harmful anthropocentric and biomedical models of health and health care. To do this, we theorize an 'environmental nursing geography' including Henri Lefebvre's idea of the production of space. Lefebvre's dialectics give us tools to ecologize space and place and further the efforts of CHNs to support the health of all people and the planet through justice and equity.